A case report of gastric emphysema induced by noninvasive positive airway pressure - Fahad Malik; Natalia Lattanzio; Karen Veloso; Jay Nfonoyim (Greater Baltimore Medical Center, 2019)
Gastric emphysema is a rare medical condition in which air penetrates any layer of the gastric wall (mucosa, submucosa, muscle layer, or serosa) due to a noninfectious source. It is essential to differentiate this from a life-threatening condition known as emphysematous gastritis. These two conditions have a similar presentation, and therefore, it is difficult to differentiate the two on imaging. Bi-level positive airway pressure (BiPAP) is a noninvasive intervention for selected patients in respiratory distress. This intervention uses positive airway pressure to prevent endotracheal intubation. The commonly noted side effects of positive airway pressure are dry mouth and oral irritation. This is the first case, to our knowledge, of gastric emphysema directly originating from BiPAP administration. It was diagnosed on imaging as pneumatosis intestinalis and emphysematous gastritis but clinical presentation was benign. The condition resolved immediately after discontinuation of BiPAP.